Synthesis, Magnetization, and Electrical Transport Properties of Mn3Zn0.9Cu0.1N - Y. Yin; J. C. Han; T. P. Ying; J. K. Jian; Z. H. Zhang; L. S. Ling; L. Pi; B. Song (Advances in Condensed Matter Physics)
We synthesized Mn3Zn0.9Cu0.1N by solid state reaction, and magnetic as well as electrical transport properties were investigated. It is found that Mn3Zn0.9Cu0.1N exhibits a first-order antiferromagnetism (AFM) to paramagnetic (PM) transition with the Néel temperature TN ~163 K, and substitution of Cu for Zn would favor ferromagnetism (FM) state and weaken AFM ground state, leading to a convex curvature character of M(T) curve. With high external fields 10 kOe–50 kOe, magnetic transition remains a robust AFM-PM feature while FM phase is completely suppressed. Thermal hysteresis of M(T) under 500 Oe is also suppressed when the magnetic field exceeds 10 kOe. Mn3Zn0.9Cu0.1N exhibits a good metallic behavior except for a slope change around TN, which is closely related to AFM-PM magnetic transition. Compared with the first differential of resistivity with respect to temperature for (dρ/dT)Mn3ZnN in transition temperature range, the absolute value of (dρ/dT)Mn3Zn0.9Cu0.1N is much lower which is close to zero.